18th world congress of basic and clinical pharmacology: thought-provoking lectures on drug safety issues. Issue 12 (2nd December 2019) - Cavero, Icilio; Holzgrefe, Henry H
ABSTRACT: Introduction : Pharmacology of the Future for Science, Drug Development and Therapeutics was the leitmotif which guided the presentations at the 18th World Congress of Basic and Clinical Pharmacology held in Kyoto in July 2018 (WPC2018). Areas covered : Of the 380 invited lectures, this report reviews the opening presentation on immune checkpoint inhibitors and three talks dealing with drug safety issues (irreproducibility of nonclinical data, clinical Phase 1 catastrophes by TGN1214 and BIA-102, 474-101 in healthy volunteers, and Phase I sentinel dosing to reduce risk to clinical study participants). Expert opinion : The nonclinical safety assessment of drug candidates preceding clinical investigations requires the adoption of more human predictable biological assays and a careful and critical analysis of all available knowledge on a candidate to ensure the safety of clinical trial participants.